Evidence-Based Practice and Chiropractic Care. (January 2013) - LeFebvre, Ron; Peterson, David; Haas, Mitchell
Evidence-based practice has had a growing impact on chiropractic education and the delivery of chiropractic care. For evidence-based practice to penetrate and transform a profession, the penetration must occur at 2 levels. One level is the degree to which individual practitioners possess the willingness and basic skills to search and assess the literature. Chiropractic education received a significant boost in this realm in 2005 when the National Center for Complementary and Alternative Medicine awarded 4 chiropractic institutions R25 education grants to strengthen their research/evidence-based practice curricula. The second level relates to whether the therapeutic interventions commonly employed by a particular health care discipline are supported by clinical research. A growing body of randomized controlled trials provides evidence of the effectiveness and safety of manual therapies.